The Paradigm of Science Integration in the Palm of Knowledge Perspective for SD NU Banat-Banin Students Lamongan - Nicky Estu Putu Muchtar; Evi Zulianah; Wahyuni Ahadiyah; Siti Khodijah (Journal of Islamic Education Research, 2023)
The birth of efforts to build the integration of science and religion at SD NU Banat-Banin Lamongan is inseparable from the phenomenon of general scientific and religious dichotomy. SD NU Banat Banin is a public educational institution with religious nuances. This research uses a qualitative approach with literature and field study. The results of this study, First; that there are 6 Morphology of palm Ilmu SD NU Banat Banin Lamongan, namely; Palm Roots (Aqidah/ideology), Palm Stems (Taqwa & Akhalakul Karimah), Palm Seeds (Students' Soul Burning), Palm Flowers (Character Education of Daily Attitudes), Palm Fruits (Achievements), and Palm Leaves (General et al.). Second, through the metaphor of the palm of knowledge, there are characteristics of the school, namely; 1). Planting Aqidah Ahlus sunnah wal jama'ah becomes the foundation of student character, 2) Apart from the Al-Qur'an and Hadith, the Yellow Book is a learning reference for students, 3) Formation of the character of the soul of students, 4) Expanding Islamic studies and avoiding dichotomies of knowledge. Learning the integration of knowledge, which in essence is to integrate the curriculum, so that the integration of general knowledge and religion as described in the 'palm Ilmu Banat-Banin' is also part of the school curriculum. This integration of knowledge has areas for improvement in its philosophy. In contrast, the curriculum conceptualized on the morphology of the palm of knowledge still needs to be categorized as the Islamisation of science.